2010
DOI: 10.1210/en.2009-1349
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Serotonin Enhances Lipid Metabolism by Accelerating Bile Acid Turnover

Abstract: Serotonin is synthesized by two distinct tryptophan hydroxylases, one in the brain and one in the periphery. The latter is known to be unable to cross the blood-brain barrier. These two serotonin systems have apparently independent functions, although the functions of peripheral serotonin have yet to be fully elucidated. In this study, we have investigated the physiological effect of peripheral serotonin on the concentrations of metabolites in the circulation and in the liver. After fasting, mice were ip injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 43 publications
(37 reference statements)
3
62
2
1
Order By: Relevance
“…Nevertheless, not all studies agree. Injection of serotonin does not impact on the uptake of 2-deoxy-glucose in the liver of fasted mice [10]. Additionally, in an experiment using conscious dogs, portal vein injection of serotonin induced hepatic glucose uptake during a hyperinsulinemic-euglycemic clamp [21].…”
Section: Serotonin and Glucose Uptake In The Livermentioning
confidence: 94%
See 3 more Smart Citations
“…Nevertheless, not all studies agree. Injection of serotonin does not impact on the uptake of 2-deoxy-glucose in the liver of fasted mice [10]. Additionally, in an experiment using conscious dogs, portal vein injection of serotonin induced hepatic glucose uptake during a hyperinsulinemic-euglycemic clamp [21].…”
Section: Serotonin and Glucose Uptake In The Livermentioning
confidence: 94%
“…Additionally, it has been reported that serotonin injection elevates plasma insulin levels [10,11]. Therefore, serotonin might regulate insulin secretion from β cells by both local and systemic actions.…”
Section: Insulin and Glucose Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Однак питання впливу цього бі-огенного аміну на секрецію жовчі, як одного із показників, що відображає функціональний стан печінки, є недостатньо вивченим. До того ж, аналіз концентрацій таких специфіч-них компонентів жовчі, як жовчні кислоти здійснювався лише у плазмі крові [11,12]. Секреція -жовчі це складний багатоетапний процес, що відбувається за участі переважно киснезалежних процесів [13], таких, зокре-ма, як синтез жовчних кислот [14].…”
Section: вступunclassified